Mapping the global election landscape on social media in 2024 - Pecile, Giulio; Di Marco, Niccolò; Cinelli, Matteo; Quattrociocchi, Walter (PloS one, 2025)
In 2024, a significant portion of the global population will participate in elections, creating an opportunity to analyze how information spreads and how users behave on social media. This study examines the media landscape on Facebook by analyzing posts from political parties and major news outlets in Europe, Mexico, and India. By identifying key topics and measuring public engagement, we uncover patterns in political discourse. Using Principal Component Analysis, we explore how these topics are related and distinguish trends in audience interaction. Our findings show how certain topics resonate differently across political groups, providing insights into the relationship between media content, political ideology, and user engagement during elections.